Suro Month Wedding Prohibition: Islamic Perspective Customary Law Debate - Alfalachu Indiantoro; Aries Isnandar; Johan Fendy Pratama; Ferry Irawan Febriansyah; Yogi Prasetyo (Al-Hayat: Journal of Islamic Education, 2022)
The Javanese tradition of avoiding marriage in the month of Suro is highly upheld, especially by the community. It is widely believed that marriage in the month of Suro will bring danger to the bride and groom, whereas in the Islamic concept, there is no prohibition against marriage in the month of Suro (Muharram). Departing from these reasons, the purpose of this study is to describe two different views of Islamic teachings and Javanese cultural traditions that have continued to contradict each other from ancient times to the present. This research is set in Ponorogo Regency, East Java. The research method used is qualitative with a sociological empirical juridical approach. The primary data used are facts about human behaviour and written documents from traditional leaders, religious leaders and related people. Using interviews and documentation for data collection, then analyzed using sociological empirical juridical. The results of the study show that the philosophical meaning of the prohibition of marriage in the month of Suro that occurs in Javanese society, especially in Ponorogo Regency, can be divided into two sides based on Paul Ricoeur's theory, namely the meaning of the prohibition from the side of the text maker and the side of the recipient/reader of the text. From the perspective of these two sides, then the philosophical meaning contained in the tradition of prohibiting marriage in the month of Suro can be concluded as a syncretism meaning between Javanese religions and cultures.